Enhancing productivity and income of small farmer through new varieties and precision farming - Balakrishna, B; Kowsalya, K S; Supriya, B B; Atheequlla, G A; Manjunath, B L; Hebbar, Shankara S (Indian Farming, 2022)
Mr. Krishna Naik of Vasappanadoddi FFP village, used to get an annual net-income of `1,86,580 from growing ragi, red gram, tomato, etc before FFP implementation with low yield due to use of local varieties, higher infestation of pest and diseases, increased labourcost, micronutrient deficiency etc in field crops and additionally multiple diseases in tomato and chilli. With DFI interventions like introduction of high yielding and disease resistant varieties in field and vegetable crops along with adoption of precision farming in tomato and chilli, he is getting an annual net-income of `6,68,420 in 2021–22, when compared to `94,000 during 2016–17. Additionally, there is cost saving of `2,21,840 in the production of tomato and chilli, due to savings in input and labour cost. He has been an inspiring link farmer for many technologies in FFP village.